Comparing Between Reading Aloud And Silent Reading In Comprehending A Text By The Eighth Year Students Of SMPN 2 Sesean - Rachel Rachel (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Kristen Indonesia Toraja, 2014)
The objective of the research is to find out the more effective between reading aloud and silent reading in comprehending a text by the eighth year students of SMPN 2 Sesean academic year 2012/2013. In order to achieve the objective of the study, the researcher designed a descriptive method. The population of this study was the second year students of junior high school of SMPN 2 Sesean. The sample of this research was class VIII I. It consists of 22 students. This research employed a cluster sampling method, the researcher took out all of the students in one class. Then, the researcher divided them into two groups. The first group answered the questions after reading aloud by the researcher while the second group answered the questions after silent reading by themselves. The result of this study revealed that silent reading scores were better than reading aloud scores. It could be seen by comparing their means. The mean of the silent reading scores was 62 while the mean of reading aloud scores was 43. The difference between the two means was 19. It means that silent reading is more effective than reading aloud in comprehending a text.In line with the result, the researcher concluded that silent reading is the effective way for students in comprehending a text.